Evaluation of the diagnostic accuracy and utility of a new dengue rapid diagnostic test in Malaysia / Chong Zhuo Lin - Chong, Zhuo Lin (2020)
Dengue is an emerging arboviral disease endemic to many tropical countries including Malaysia. Due to its unspecific symptoms, dengue diagnosis can only be confirmed through diagnostic tests. Existing laboratory-based dengue diagnostics like enzyme linked immunosorbent assay (ELISA) is accurate in detecting dengue non-structural protein-1 (NS1), and anti-dengue immunoglobulin M (IgM) and G (IgG); but is also more complicated and time-consuming. Commercially available dengue rapid immunochromatographic test (RIT) is efficient but less sensitive. A new dengue rapid diagnostic rest (RDT) using biosensors may be both efficient and accurate in diagnosing acute dengue. This study evaluated this new dengue NS1-based RDT and compare its diagnostic accuracy and utility with a NS1/IgM/IgG combo RIT using a phase III diagnostic evaluation study design. It also examined the effect of various study characteristics on test performance. Firstly, a systematic review and meta-analysis was performed to review the performance of various RITs for the diagnosis of acute dengue. The effect of various study characteristics on test performance was explored through subgroup and sensitivity analyses. Secondly, after a case-control pre-test of the new RDT in a laboratory on archived samples found it to be useful; it was evaluated together with a RIT in a cross-sectional study in a public clinic on prospectively and consecutively recruited patients for the diagnosis of acute dengue infection, using established laboratory tests as reference standard. Subgroup analyses was also performed parallel to that of the systematic review. The systematic review and meta-analysis identified SD Bioline Dengue Duo as the most evaluated RIT with rather good performance. Study design, virus serotype, previous dengue exposure, disease phase, RIT brand, and reference test, were found to modify test accuracy. In the primary study, the sensitivity (SN) and iv specificity (SP) of the new RDT – ViroTrack Dengue Acute NS1, were 62.3% (95%CI 55.6-68.7) and 95.0% (95%CI 91.7- 97.3), as compared to that of SD NS1/IgM/IgG combo RIT at 82.4% (95%CI 76.8-87.1) and 87.4% (95%CI 82.8-91.2) (both p<0.001), respectively. In addition, NS1/IgM/IgG combination would produce less false negatives compared to NS1-only test. The pattern by which different study characteristics affected test performance was found to be similar in both the review and primary study. Although ViroTrack had rather good diagnostic performance and utility, it had significantly lower SN compared to SD NS1/IgM/IgG RIT. Hence, the latter was superior to ViroTrack as it would miss less dengue patients. Detection of more dengue patients allows clinical management and vector control activities to be administered where they are needed, thus reducing disease mortality and morbidity. Future combination of serology components to ViroTrack has to be evaluated anew together with currently available RIT using phase III cross-sectional design with consecutive sampling, and proven more accurate, before it can be considered better alternatives to the existing ones. Keywords: dengue, rapid diagnostic test, biosensors, evaluation, diagnostic performance